Double‐Object Constructions in Romance: The Common Denominator. (6th February 2020) - Pineda, Anna
Abstract: This article presents empirical and theoretical arguments that challenge several received ideas regarding double‐object constructions in Romance languages. First, I argue that the syntactic and semantic differences that, according to much prior literature, hold between Spanish ditransitives with and without dative clitic doubling do not hold, at least for many speakers. Specifically, there are nondoubled Spanish ditransitives that are to be analyzed as double‐object constructions, not as prepositional constructions; the optional presence of dative clitic doubling in double‐object constructions reduces to a mere surface difference of spellout of the Low Applicative head that relates the indirect object and the direct object and is responsible for the transfer‐of‐possession interpretation. Next, I explore some theoretical consequences of these novel empirical observations regarding dative clitic doubling, showing that arguments for a base structure for Spanish/Romance double‐object constructions in which the direct object is higher than the indirect object are not viable, since in the absence of dative clitic doubling it is not possible to account for the c‐command facts. Lastly, I show that my analysis of double‐object constructions extends to other languages in the Romance family where dative clitic doubling in ditransitives is optional, such as Catalan, as well as to Romance languages that do not have dative clitic doubling but arguably do have double‐object constructions, such as French and Italian.